2014
DOI: 10.1016/j.jaapos.2014.07.176
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of the Spot Vision Screener in detecting amblyopia risk factors

Abstract: Background The purpose of this study was to evaluate the updated Spot Vision Screener (PediaVision, Welch Allyn, Skaneateles Falls, NY) in detecting amblyopia risk factors using the 2013 guidelines of the American Association for Pediatric Ophthalmology and Strabismus (AAPOS). Methods In this prospective study, patients seen from June 2012 to November 2013 were tested with the Spot prior to examination by a pediatric ophthalmologist who was masked to test results. The following data were analyzed: age, subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
48
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(51 citation statements)
references
References 14 publications
1
48
1
1
Order By: Relevance
“…26 As in the present study, the Spot had a higher success rate in providing estimates of refractive error in two of three studies that directly compared the two instruments. 2,3,5 However, the success rate for the Plusoptix in the present study was much lower than observed in pediatric ophthalmology clinic samples, suggesting that the low success rate we observed was due to the high rate of astigmatism in our study population.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…26 As in the present study, the Spot had a higher success rate in providing estimates of refractive error in two of three studies that directly compared the two instruments. 2,3,5 However, the success rate for the Plusoptix in the present study was much lower than observed in pediatric ophthalmology clinic samples, suggesting that the low success rate we observed was due to the high rate of astigmatism in our study population.…”
Section: Discussionsupporting
confidence: 64%
“…26 In addition, when using a composite examination-positive definition (eg, “astigmatism or hyperopia or myopia or anisometropia”), the same instrument version and same criteria may still yield different specificity and sensitivity for the composite outcome in populations with different relative prevalences of the different types of refractive error. Reports of sensitivity across studies has been good for both instruments (>80%), although specificity has varied most likely due to differences in study populations (age range, presence of ocular abnormalities, inclusion of children with developmental delay, etc).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Photoscreening has been shown to have high sensitivity and specificity in community and office settings. [14][15][16][17][18][19][20] Photoscreening instruments assess both eyes simultaneously and the images can be interpreted by trained operators, by a central reading center, or with computer software.…”
Section: Instrument-based Screening Techniquesmentioning
confidence: 99%
“…24 Rapid vision screening methods have previously been proposed for adults. 25 However, such methods often involve computer-assisted tools and are not portable. In contrast, the Spot ™ Vision Screener (Welch Allyn Inc.) is a handheld unit that provides rapid measurements and has been validated in the detection of risk factors for amblyopia and uncorrected refractive errors in children.…”
mentioning
confidence: 99%